Comparative study of low dose aspirin versus combination of low dose aspirin and low molecular weight heparin in idiopathic recurrent pregnancy loss - Rekha, S. Bhanu; Chandra, K. Sharath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To compare the role of low dose aspirin versus combination of low dose aspirin and low molecular weight heparin in idiopathic recurrent pregnancy loss and assess the effectiveness of low dose aspirin and low molecular weight heparin in having a better obstetric outcome. Methods: This study was conducted in a private hospital in Mahabubnagar from June 2017 to May 2019. A total of 80 pregnant ladies who had previous 2 and or more pregnancy losses in the early (before 20 weeks) or late (after 20 weeks) pregnancy period was included in the study. 80 pregnant women with idiopathic/unexplained recurrent pregnancy loss were properly evaluated in regard to the history of previous period of gestation of loss, previous scans in regard to documentation of fetal pole and gestation, cardiac activity, anomaly scan and growth scan and any special investigations in previous pregnancies and present pregnancy. Results: A total 80 pregnant women with previous 2 and more unexplained pregnancy losses who were evaluated and found negative with major causes of pregnancy losses half of them (40) were treated with low dose aspirin alone and the other 40 women were treated with a combination of low dose aspirin (75 mg) and low molecular weight Heparin (20 mg) daily low molecular weight heparin till term. The aspirin alone group had 82.5% live birth rate and the combination group had 92.5% live birth rate which is quite satisfactory and more than the Aspirin alone group. Conclusions: Use of combination of low dose aspirin and low molecular weight heparin seems to be a good choice of drugs in treating the unexplained recurrent pregnancy losses than low dose aspirin alone.